Quality is the best recipe! - Weiß, Reinhold [Verfasser] (My University, 2007)
The article explains, why also in a time when in-company training places are in short supply, the issue of quality should be put on the agenda. (BIBB)
Keywords: L 6.2 Qualitätsmanagement/Qualitätssicherung; S 1.3.1 Ausbildung im Dualen System; Qualitätssicherung; Berufsbildung